Creating Competitive Markets for Service Delivery : Policy Options and Country Experiences - Agapitova, Natalia (World Bank, Washington, DC, 2017)
Social enterprises (SEs) are defined as private organizations that use business approaches to achieve social, environmental and economic outcomes. The number of SEs providing social services has grown rapidly across the world, and is reaching sizeable populations. This note is prepared at the request of the Ministry of Finance (MoF) of Russian Federation to support drafting and implementation of new law on outsourcing municipal social services. The note is part of the technical assistance provided to the Ministry of Finance (MoF). This note explores various policy options for engaging social enterprises as services providers and creation of a competitive market for service provision in Russia. In particular, the MoF expressed interest to learn from examples of Canada, Germany, France, Sweden, United Kingdom (UK) and United States (US).